2002
DOI: 10.1002/cncr.10453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of delay to diagnosis on prognostic indicators of screen‐detected breast carcinoma

Abstract: BACKGROUND Although delay to diagnosis after a breast screening abnormality causes anxiety, its effect on prognosis is unknown. METHODS Using pooled data from five Canadian organized breast cancer screening programs, the authors used unconditional logistic regression to evaluate the effect of delay to diagnosis on prognostic indicators among 4465 women with invasive breast carcinoma diagnosed in the ipsilateral breast within 3 years of an abnormal screen performed during 1990–1996. RESULTS Women with high‐susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
3
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 30 publications
9
82
3
12
Order By: Relevance
“…The tumour stages of breast cancers with a delayed diagnosis in our study were more favourable compared with cancers diagnosed within 3 months of a positive screen. In contrast, a Canadian study showed that screen-detected breast cancers diagnosed between 20 and 52 weeks after mammographic screening more often had a larger tumour size or lymph node metastases compared with breast cancers diagnosed within 4 -12 weeks of an abnormal screen (Olivotto et al, 2002). Our findings may be explained by diagnostic suspicion bias: the workup may have been more aggressive for mammographic features highly suggestive of cancer.…”
Section: Discussioncontrasting
confidence: 83%
“…The tumour stages of breast cancers with a delayed diagnosis in our study were more favourable compared with cancers diagnosed within 3 months of a positive screen. In contrast, a Canadian study showed that screen-detected breast cancers diagnosed between 20 and 52 weeks after mammographic screening more often had a larger tumour size or lymph node metastases compared with breast cancers diagnosed within 4 -12 weeks of an abnormal screen (Olivotto et al, 2002). Our findings may be explained by diagnostic suspicion bias: the workup may have been more aggressive for mammographic features highly suggestive of cancer.…”
Section: Discussioncontrasting
confidence: 83%
“…In industrialized countries such as Canada, Norway, Sweden and the United Kingdom, only between 8% and 22% of patients are diagnosed with locally advanced breast cancer [16].…”
Section: ) Presentation Delay and Stage At Diagnosismentioning
confidence: 99%
“…Diferenças de sobrevida podem ser explicadas pelos estágios mais avançados ao diagnóstico nos países em desenvolvimento 5 . Estudos têm demonstrado, também, que fatores como a falta de acesso aos serviços de saúde, os atrasos na investigação de lesões mamárias suspeitas e na efetivação do tratamento da doença têm contribuído para o diagnóstico e tratamento tardios e, consequentemente, para a elevada mortalidade por câncer de mama [6][7][8][9] . O prognóstico das pacientes está intimamente relacionado ao estadio em que os tumores são diagnosticados.…”
Section: Introductionunclassified